Strategi Kantor Urusan Agama dalam Menangani Pernikahan Dini di Kelurahan Tetebatu Kecamatan Pallangga Kabupaten Gowa: Perspektif Maqasid al-Syariah - Rahim, Irawati; Ridwan, Muh. Saleh; Cahyani, Andi Intan (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem of this research is what is the strategy of the Office of Religious Affairs in dealing with the rise of early marriage from the perspective of Maqasid Al-Sharia in Tetebatu Village, Pallangga District, Gowa Regency. The type of research used in this study is field research that is descriptive analytic. The source of this study is the Office of Religious Affairs and Early Marriage Couples. Furthermore, the data collection methods carried out are observation, interviews, and documentation. Then data management techniques and data analysis are carried out through data reduction, and conclusion or verification. In this study, it can be concluded that the Office of Religious Affairs in Handling Early Marriage in Tetebatu Village, Pallangga District, Gowa Regency is socializing the law on marriage age to the community. Then make a refusal and no tolerance for underage registrants who do not have a clear reason, then counseling related to the impact of early marriage online through youtube social media and health counseling. Maqasid Al-Sharia's view on Early Marriage in Tetebatu Village, Pallangga District, Gowa Regency is that underage marriage can cause various diseases. Starting from cervical cancer, cervical cancer, to the risk of HIV + / AIDS. Based on this, it can be concluded that early marriage is contrary to the principle of Hifz al-Nafs (nurturing offspring).